(untitled) (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
Caisim plants are one of the vegetables that are favored by many people. Hydroponics can be an alternative for more effective and efficient caisim cultivation. Hydroponics requires AB Mix nutrition as a source of nutrients for plants. AB Mix nutrition that is available has a relatively high price, there needs to be another alternative, namely bamboo shoot POC to reduce AB Mix nutrition and still provide nutrients for plants. The purpose of the study was to determine the effect of bamboo shoot liquid organic fertilizer on the growth and production of hydroponic caisim plants. The research was conducted from October to December 2023, at the Hydroponic Installation of the Payakumbuh State Agricultural Polytechnic Campus. This study used a completely randomized design method with 5 treatments and 4 replications simultaneously. The population was 180 plants and the sample was 80 plants using the Nutrient Film Technique (NFT) installation type. Data analysis using Anova test followed by Duncan Multiple Range Test (DMRT) 5% using SPSS 20 software. The results showed that the application of bamboo shoot POC and AB Mix to the growth and production of hydroponic caisim was significantly different on the parameters of leaf width, leaf length, plant height, stem diameter, root length and production yield, but not significantly different on the number of leaves. The treatment with the best value by giving POC is 75 ml bamboo shoot POC + AB Mix 50%, although the results cannot be as good as the control treatment.